Analysis the Level of Experience of Technology Users’ Perspectives on LinkedIn Websites - Ibrahim, Aghi Kalam; Supriyatin, Wahyu; Rianto, Yasman (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2024)
LinkedIn is a web-based application that can be used by job seekers, both new users and professional users. LinkedIn website is not only used by job seekers but can be used for various other activities. Application user experience is a major assessment of the quality of the software. LinkedIn website user experience can be seen by measuring the website using several aspects. This research aims to analyze the website user experience using the User Experience Questionnaire (UEQ) method. Measurement using the UEQ method is seen by using six aspects of the measurement scale, namely attractiveness, clarity, efficiency, accuracy, stimulation and novelty. Data collection in the study was carried out using a questionnaire given to 41 respondents totaling 26 questions. The questionnaire data will be processed using UEQ Data Analysis Tools. The results of UEQ measurements with benchmark comparisons show four aspects that are in the below average category, namely attractiveness, efficiency, stimulation and novelty. While two aspects are in the bad category, namely clarity and accuracy. So it is necessary to develop and improve the LinkedIn website by developers related to aspects that are in the bad category. The two bad aspects have a value of 0.58 for the clarity aspect and 0.53 for the accuracy aspect.